Ecological momentary assessment of contextual variables, satisfaction, and emotional and behavioral states of adolescents by level of victimization. (June 2018) - Magallón-Neri, E.; Kirchner, T.; Forns, M.; Calderón, C.; Planellas, I.
Abstract: The harmful effects of victimization on mental health have been demonstrated in several age groups, cultures, and populations, but there is wide variability in the resulting psychopathology. Ecological momentary assessment (EMA) allows the expression of an emotional state to be recorded at any given time and linked to a situation or context. This study aimed to analyze the contextual variables (where, with whom, and what), momentary satisfaction, and perception of momentary emotional and behavioral symptoms in a cohort of adolescents by the level of victimization, using EMA. We explored the everyday symptom profiles and the contexts in which events took place among 100 adolescents over a one-week period. Sociodemographic data were collected and assessment was done using the EMA (as a smartphone application) and the Juvenile Victimization Questionnaire (to assess childhood and adolescent victimization). In this study, regarding contextual variables, the group with the highest level of victimization (top 10%) showed a significant relationship with being away from home and being with friends other than classmates, and not being with parents or relatives. There was also an unexpectedly higher frequency of sporting engagement in this group. A relationship existed between emotional and behavioral problems and higher levels of victimization. In conclusion, the different groups of victimized subjects present a relatively high level of satisfaction in relation to the daily contexts and show low levels of emotional and behavioral symptomatology.